Pengaruh Green Innovation terhadap Environmental Performance dan Copetitive Adventage - Rahayu; Rini Armin; M Adik Rudiyanto (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
This study aims to examine the effect of Green Innovation on environmentally sensitive performance. Green Innovation includes the sub-dimensions of green product innovation and green process innovation, while environmentally sensitive performance. has two sub-dimensions as environmental performance and competitive adventage. The sample of this research is batik SMEs in East Java that apply Green Innovation. The sample size is 221 batik SMEs which was carried out by random sampling technique. The results of testing the hypothesis through the Pearson Correlation data analysis technique show that there is a significant relationship between green innovation and environmental performance. In addition, green innovation also affects environmental performance and competitive adventage. The effect of green innovation on environmental performance was found to be higher than competitive adventage. This study reveals that, batik SMEs that apply green innovation receive positive perceptions and opinions from various groups, especially consumers who are fanatical about batik products that have a high level of environmental concern.